Maternal levels of growth differentiation factor-15 in patients with preeclampsia - Ilkbal Temel Yuksel; Begum Aydogan Mathyk; Berna Aslan Cetin; Ugur Turhan; Zihniye Gonca Okumus; Gonca Yetkin Yildirim; Deniz Kanber Acar (Taylor & Francis Group, 2018)
Objective: Growth differentiation factor-15 (GDF-15) is a stress-induced cytokine and related to the prognosis of cardiovascular diseases. Our purpose is to measure the maternal levels of GDF-15 in patients with early-onset preeclampsia (EOPE) and late-onset preeclampsia (LOPE). Methods: This cross-sectional study was conducted including 72 pregnant women, 23 with normal pregnancies and 49 with preeclampsia (26 with EOPE and 23 with LOPE). Maternal serum levels of GDF-15 were measured by using enzyme-linked immunosorbent assay kits. Results: The median serum GDF-15 level was found to be the highest in the EOPE group (EOPE: 441.7 pg/ml). The median serum GDF-15 levels were higher in women with preeclampsia than in the control group (309.7 pg/ml vs. 436.6 pg/ml, p: 0.009). Conclusion: Our findings suggest GDF-15 increased as a response to endothelial injury caused by cytokines triggered by preeclampsia.